Book Review Globalization and Cultural Diversity - Hamid Sajadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Globalization is accompanied by the expansion of mass communication across the globe. Regarding the magnitude and type of the significant impacts left by globalization and cosmopolitan connections on cultural developments, various theories have been formed, among which the most important we can refer to the theory of cultural convergence and the theory of cultural polarization. The main issue is the relationship between cultural diversity and globalization, which Norris and Inglehart have tested in their book, Cosmopolitan Communications: Cultural Diversity in a Globalized World, through an extensive survey based on variables such as the use of the news media, cultural values, liberal views, and secularism. According to the results of this study, globalization has had a convergent aspect only in the areas close to the center of the mass communications world, while the fact is that due to the so-called firewalls, a major part of the world is not highly exposed to global mass communications. The result is that, despite the prevalence of the globalization process, the main core of national cultures still remains in the world. The present paper tries to review and examine the relationship between globalization and cultural diversity introduced in the collaborative research of Norris and Inglehart, which is translated into Persian by Abdollah Fazeli and Sajedeh Allameh and published in a book entitled “Globalization and Cultural Diversity” by Kavir Publishing. In addition to the review and analysis of the content of this work, its form and translation are also considered in this paper.